Analisis Pengaruh Current Ratio (CR), Collateralizable Assets (COL), Return On Equity (ROE), dan Growth Terhadap Dividend Payout Ratio (DPR) (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Periode 2005 - 2011) - Liwe, Gretty Brigitta (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2014)
Dividend policy is a policy of the company to be aware and careful consideration. In the dividend policy determined amount of profit allocation that can be distributed to shareholders (dividends) and the allocation of retained profits to the company. The greater the retained earnings, the smaller the dividend to be distributed to the shareholders. In the allocation of income arises various problems encountered. Announcement of the distribution of dividends by a company is a signal to shareholders. This study aims to determine the effect of the Current Ratio (CR), Collateralizable Asset (COL), Return on Equity (ROE) and the Growth of the Dividend Payout Ratio (DPR) Studies on the Indonesia Stock Exchange Period 2005-2011. The population in this study is the Company's Financial Statements listed on the Stock Exchange the share dividend. The samples are 8 companies during 2005 - 2011. The research instrument used secondary data and processed using SPSS 20, with the method of analysis used is multiple linear regression analysis. Results of statistical research concludes that the Current Ratio, Collateralizable Assets, Return on Equity, and Growth together no significant effect on Dividend Payout Ratio on manufacturing companies in Indonesia Stock Exchange, also partially, Current Ratio, Collateralizable Assets, Return on equity, and Growth no significant effect on Dividend Payout Ratio on manufacturing companies in Indonesia Stock Exchange. The suggestion of this study is to further research, this study only uses the sample derived from a manufacturing company that can not necessarily be generalized to other industries. This is due to the limited time of the study. It is recommended in future studies could be expanded scope of research-type kejenis other industries also added the study variables such as Debt to Equity Ratio (DER), Return on Equity (ROE), and the ratio - the ratio of the other. And also expected in future studies to add a longer time span.